Characteristics of transient processes in a silver nanowire with optically dynamic shell - Stognii, N.P.; Klimova, N.P.; Butenko, N.S. (Radiotekhnika, 2018)
Fundamental theoretical understanding of the process of the time domain dynamics of the surface plasmon excitation in the structure, consisting of a metal nanowire coupled with the optically dynamic shell is presented. Details are described of the dynamics in the metal nanowire by means of meticulous and exact mathematical calculations that found from the semi-analytic solution into the Laplace transform domain and its accurate inversion into transient domain by virtue of residues assessment at singular points that correspond to the excited plasmons of the structure. This problem is a 2D model of nanolaser and has applications in the most growing areas of nanophotonics that require technologies, which can stimulate coherent plasmon fields in subwavelength domain.